From genes to conservation: The potential of genetic resources of Amphibian in Malaysia for next generation monitoring and conservation strategies - Ramli, Farah Farhana; Munian, Kaviarasu; Othman, Nursyuhada; Haris, Hidayah; Sariyati, Nur Hartini; Najmuddin, Mohd Faudzir; Mahyudin, Nur Aina Amira; Abdullah-Fauz, Nurfatiha Akmal Fawwazah; Abdul-Latiff, Muhammad Abu Bakar (2024)
Genetic monitoring plays a crucial role in the conservation management of amphibians due to their vulnerability to habitat changes. Traditional biodiversity monitoring methods, such as trapping and morphological identification, are being complemented by advanced technologies that enhance species identification sensitivity and monitoring capabilities. Genetic resource availability is essential for effective amphibian biodiversity assessment and monitoring. This study aims to evaluate the current state of genetic resources and their comprehensiveness for amphibian biomonitoring and conservation in Malaysia. The study focused on seven targeted mitochondrial DNA loci, and data regarding these loci were obtained from the National Centre for Biotechnology Information (NCBI) database. The results showed that 69.8% of amphibian species in Malaysia had genetic data available for at least one or more of the targeted genes, with the 16S gene being the most widely represented. However, only 12.1% of threatened species and 61.2% of endemic species had accessible genetic information. Biological utilization was identified as the primary threat to amphibian species in Malaysia, accounting for 27.0% of recorded threats. These findings highlight the need for further improvement in achieving comprehensive genetic resource information for amphibians in Malaysia. Advancements in enpromisesntal DNA (eDNA) analysis and Next Generation Sequencing (NGS) technologies hold promise in enhancing efforts to conserve amphibian diversity. It is crucial to continue expanding genetic resources to support ongoing monitoring and preservation initiatives for amphibians in Malaysia, ensuring effective conservation management.